Circuitos de acionamento para iluminação semicondutora empregando topologias integradas com capacitores de longa vida útil - Cosetin, Marcelo Rafael (2013)
This work presents an analysis and design of two Light Emitting Diode (LED) drivers topologies based on static switched converters aiming to avoid using electrolytic capacitors. Considering the low lifetime of electrolytic capacitors compared to LEDs, the topologies aims for reducing the storage capacitance and replaces it by a longer lifetime capacitor, increasing the overall system life span. A Proportional Integral controller is designed to reduce the output current ripple. Consequently, it reduces the bus voltage ripple which allows working with reduced bus capacitances. The input current harmonic distortion limit must be observed. The power factor correction stage is based on a Single Ended Primary Inductance Converter (SEPIC) operating under discontinuous conduction mode (MCD) for both topologies. The power control (PC) stage is performed by a Buck converter for the SEPIC-Buck topology and by a Ćuk converter for the SEPIC-Ćuk topology. These PC converters present output current source behavior, suitable for LED application. Two LED driver prototypes are implemented and the results present high efficiency and a 50% current ripple on the LED. Furthermore a simple dimming strategy is proposed and implemented.